Comparative Language Style Of Moses Story In Al-Quran - Romdani Yumna Rasyid Aceng Rahmat (Arabic Education Program IAIN Pekalongan, 2018)
The purpose of the study is to find the comparative language style of Moses Story in Al-Quran. Then, the people knew the context meaning of the story to implement in the real life. The research method is qualitative using content analysis. The data used in this study are the verses of Al-Quran. Comparative language styles contained in the verses of the story of Moses in the AL-Quran include the style of personification, allegory, periphrasis, simile, hyperbolic, metaphorical, synesthetic, litotes, allusion, symbolic, and synecdoche. The commonly used language style comparison is the allusion language style